Occupational lifting and pelvic pain during pregnancy: a study within the Danish National Birth Cohort - Pernille Stemann Larsen; Katrine Strandberg-Larsen; Mette Juhl; Susanne Wulff Svendsen; Jens Peter Bonde; Anne-Marie Nybo Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: Pelvic pain during pregnancy is a common ailment, and the disease is a major cause of sickness absence during pregnancy. It is plausible that occupational lifting may be a risk factor of pelvic pain during pregnancy, but no previous studies have examined this specific exposure. The aim of this study was to examine the association between occupational lifting and pelvic pain during pregnancy. METHODS: The study comprised 50 143 pregnant women, enrolled in the Danish National Birth Cohort in the period from 1996-2002. During pregnancy, the women provided information on occupational lifting (weight load and daily frequency), and six months post partum on pelvic pain. Adjusted odds ratios for pelvic pain during pregnancy according to occupational lifting were calculated by logistic regression. RESULTS: Any self-reported occupational lifting (>1 time/day and loads weighing >10 kg) was associated with an increased risk of pelvic pain during pregnancy as compared to no such lifting. A confounder-adjusted exposure-response relation was observed between self-reported total loads lifted and pelvic pain during pregnancy. Daily lifting of both medium (11-20 kg) and heavy loads (>20 kg) were associated with increased risk, and the highest risk was observed among women who lifted heavy loads independent of exposure to medium loads. CONCLUSION: Occupational lifting may increase the risk of pelvic pain during pregnancy.